ANALYSIS OF ADOLESCENT FISH CONSUMPTION LEVELS AT VOCATIONAL HIGH SCHOOL LEVEL IN MEJAYAN DISTRICT, MADIUN REGENCY - Agnes Puspitasari Sudarmo; Abdul Kohar Mudzakir; Haendra Kusuma Putra Ashad (Jurnal Perikanan Unram, 2024)
School-age adolescents, especially vocational high school students, need sufficient nutritional intake because their learning system demands physical activity, namely practice. Fish contains quite high protein and fatty acids which affect nutritional status and academic achievement. Adolescent fish consumption in Mejayan District is relatively low. Many factors influence it, such as: parental income, maternal education, taste, perception of fish prices, knowledge about fish, and social media. This study aims to analyze the factors that influence fish consumption. The design of this study is a cross-sectional study with data collection through filling out questionnaires and interviews using the FFQ and 24-hour Food Recall methods. The Adjusted R2 value is 0.438. The results of the hypothesis test show that taste factors, fish prices, and fish knowledge have a significant effect on the level of fish consumption as indicated by the sig. <0.05. Factors that do not have an effect are parental income, maternal education, and social media as indicated by the sig. >0.05.